Design Principles of Multi-Chambered Gun - Michal KOVAŘÍK (Problemy Mechatroniki, 2016)
The multi-chambered gun concept is based on the effect of increasing muzzle velocity of weapon system without need of new technologies or excessive dimensions. The mathematical model of interior ballistics of the multi-chambered gun was assembled by means of extension and modification of the thermodynamic model of interior ballistics of conventional gun. The reliability of numerical solution of a model has been examined in the comparison with results of ballistic shootings with several arrangements of the experimental weapon system. Subsequently the numerical sensitivity analysis of the interior ballistics model has been carried out as well as the simplified system of analytical approximate expressions comprising the crucial gun design characteristics has been built up. Outputs of both the sensitivity analysis and simplified system could be used in the case of multi-chambered gun designing in order to reach maximum velocity with no simultaneous rise in maximal ballistic pressure.